PENGARUH TINGKAT PARTISIPASI KELAS TERHADAP KINERJA AKADEMIK MAHASISWA - Anggita Langgeng Wijaya (Universitas Negeri Yogyakarta, 2012)
This research tests the influence degree of class participation on academic performance. Population of this research is all of new student at first semester from accounting education department at IKIP PGRI Madiun. In this study, sample consist 109 students from three introduction business class. Hypothesis test of this research uses simple regression analysis. The results show that class participation positively affects on student academic performance.